A Low Signal Detection of X‐Rays From Uranus. Issue 4 (31st March 2021) - Dunn, W. R.; Ness, J.‐U.; Lamy, L.; Tremblay, G. R.; Branduardi‐Raymont, G.; Snios, B.; Kraft, R. P.; Yao, Z.; Wibisono, A. D.
Abstract: Within the solar system, X‐ray emissions have been detected from every planet except the Ice Giants: Uranus and Neptune. We analyze the three archival Chandra X‐ray observations of Uranus (each 24–30 ks duration) to date: a stand‐alone Advanced CCD Imaging Spectrometer (ACIS) observation on August 7, 2002 and two High Resolution Camera (HRC) observations on November 11 and 12, 2017 coordinated with optical observations. For the earlier ACIS observation, the Uranus‐coincident photons were clustered in the 0.6–1.1 keV spectral range, consistent with emission from Jupiter and Saturn. To test the significance of the detected signal, we distributed a grid of ∼10, 000 Uranus‐sized regions across the field of view (FoV). The number of Uranus‐coincident X‐ray photons in the 0.5–1.2 keV range exceeded 99.9% of Uranus‐sized regions across the FoV (10.2 standard deviations > FoV mean; probability of chance occurrence ∼10 −6 –10 −7 ). However, the planetary signal was low with only 5 ± 2.2 X‐ray photons against a FoV mean background of 0.16 photons. Without the possibility of energy filtering, the recent HRC observations had a much brighter background (FoV mean ∼10 photons). Consequently, neither of the new observations provided a second unambiguous Uranus detection, although a 40‐min interval of brightening on November 12, 2017 did produce a signal above 99.9% of the FoV. The observed Uranus X‐ray fluxes of 10 −15 –10 −16 erg/cm 2 /s are consistent with previous observational limits and modeling predictions. These fluxes exceed expectations from scattered solar emission alone, suggesting either a larger X‐ray albedo than Jupiter/Saturn or the possibility of additional X‐ray production processes at Uranus. Further observations are needed to test this. Key Points: A Chandra ACIS observation reveals a 10.3 sigma detection of X‐rays from Uranus with a probability of chance occurrence of 10 −6 –10 −7 Uranus' X‐rays are concentrated between 0.6 and 1.1 keV, consistent with emission observed from Jupiter and Saturn The X‐ray fluxes seem to exceed scattered solar emission alone, which may suggest X‐ray aurora and/or X‐ray fluorescence from the rings